Inhibition of the sodium-glucose co-transporter 2 in the elderly: clinical and mechanistic insights into safety and efficacy - Cintra,Riobaldo (2019)
SUMMARY The prevalence of type 2 diabetes mellitus (T2DM) in the elderly grew sharply over the last decade. Reduced insulin sensitivity and secretory capacity, weight gain, sarcopenia, and elevated adiposity are all common metabolic and body changes in the aging population that favor an increased risk of hypoglycemia, frailty syndrome, falls, and cognitive dysfunction. First line antidiabetic therapy is frequently not safe in older individuals because of its high risk of hypoglycemia and prevalent co-morbid diseases, such as chronic kidney disease, osteoporosis, cardiovascular disease, and obesity. Sodium-glucose cotransporter 2 inhibitor (SGLT2i) is a new class of antidiabetic therapy that inhibits glucose and sodium reabsorption on renal proximal convoluted tubule. Its effect is well demonstrated in various clinical scenarios in the younger population. This review and metanalysis describe particularities of the SGLT2i on the elderly, with mechanistic insights of the potential benefit and remaining challenges about the use of these drugs in this important age group. Further, we will present a meta-analysis of the main effects of SGLT2i reported in post-hoc studies in which the median age of the subgroups analyzed was over 60 years. Despite the absence of specific clinical trials for this population, our findings suggest that SGLT2i therapy on older individuals is effective to lower glucose and maintain its effect on systolic blood pressure and body weight.